APPLICATION OF INTRAORAL SCANNERS IN PROSTHETIC TREATMENT OF EDENTULOUS PATIENTS - Zhanina Pavlova (Romanian Society of Oral Rehabilitation, 2023)
Introduction: Digital impressions have numerous advantages compared to the traditional techniques and intraoral scanners have wider and wider application in prosthetic dental practice. When it comes to elaborating complete dentures, the intraoral scanning of fully edentulous jaw is still challenge dew to some special features that make difficult the achievement of high quality digital impression. The present review research the applicability of intaoral scanners in prosthetic treatment of edentulous patients considering the present technological development.